The Making of State Homosexuality: How AIDS Funding Shaped Same-Sex Politics in France. (November 2017) - Broqua, Christophe; Fillieule, Olivier
The article traces the way AIDS activism, and more largely the homosexual movement, have been progressively supported and funded by the State in France. If the State is most often viewed as a target of protest movements, some research focuses on how state interventions may contribute not only to the development and success of voluntary groups but also constrain their room to maneuver, pushing them to soften their claims, their identities and their repertoires of action. The authors also address a less often explored dimension of the effect of State funding, that is, how, in the case under study, it has contributed to shaping the social and legal forms of same-sex politics and coproduced social norms of contemporary homosexuality. State funding is viewed less as a factor of transformation of movements, in its effects of acting as a brake on or a facilitator of action by mobilized groups, and more in the way it has become involved in a process of coproduction of social norms along with social movements.